Distribution of blood lead and cadmium levels in healthy children aged 0 to 18 years and analysis of related influencing factors in Henan, China: data findings from 2017 to 2022 - Hui Yan; Bo Zhai; Ruiling Feng; Penggao Wang; Fang Yang; Yang Zhou (Italian Journal of Pediatrics, 2024)
Abstract Background There is still a lack of data on blood lead levels (BLLs) and blood lead levels (BLLs) in healthy children of all ages from 0 to 18 years in China. This study was performed to analyze the BLLs and BCLs in healthy children aged 0-18 years from 2017 to 2022 in urban and rural areas of Henan Province, Central China, as well as their relationships with socio-demographic variables and certain relevant exposure factors. To provide a basis for evaluating public health policy development and exposure risk management. Methods This was an observational study containing data from 17 prefecture-level cities in Henan, China. Blood Pb and Cd levels were determined using a triple quadrupole inductively coupled plasma mass spectrometer equipped with an autosampler. We first calculated the concentrations of Pb and Cd elements in participants of different genders, ages and years, and then created visual graphs depicting the distribution of each element in terms of gender, age and year (2017-2022). The rates between different groups were compared using the Chi-square test or Fisher exact test (if applicable). The means were compared by one-way ANOVA, medians were compared with the Kruskal-Wallis rank-sum test. Generalized linear models (GLM) were performed to estimate the effects of various factors on blood Pb and Cd concentrations in children. Results We recruited a total of 25,920 children (16,142 boys and 9,778 girls) aged 0.01 to 18.00 years (2.58 (1.00,6.25)). The median of BLLs was 23.48µg/L, around 9.39% of studied children had elevated BLLs. The median of BCLs was 0.66µg/L, around 1.84% of studied children had elevated BCLs. The median blood Pb concentration was higher in boys (23.90µg/L) than in girls (22.75µg/L) (P<0.001). The median blood Pb concentration was highest in the 3-7 years group (24.51µg/L) and the median blood Cd concentration was highest in the 1-3 years group (0.66µg/L) among all age groups. Both BLLs and BCLs were substantially higher in children in 2020-2022 compared to 2017-2019. Rural children had lower BLLs and higher BCLs. The results of the generalized linear model showed that children in households using Oil, coal, pellet or other wood as a fuel for heating, children with higher frequency of exposure to tobacco smoke and beverage intake had significantly increased chances of elevated BLLs and BCLs. Conclusions Pb and Cd exposure of children in this area is relatively low, but associated risk factors continue to exist in vulnerable populations. This study is the first big data analysis of Pb and Cd in children in Henan, China, and provides baseline information for future research.